# 2(x-3)-3(x+5)=3(x-2)-7 x=-2, i need to check and I can't get it to work.?

Question:x=-2 and I've tried plugging it in and can't get it to work. Any help or thoughts would be greatly appreciated. maybe x doesnt really equal -2 and it's a trick.

Watch:
2(-2-3) -3(-2+5) = 3(-2-2)-7
2(-2 + -3) -3(3) = 3 [(-2+(-2)] -7
2 (-5) - 9 = 3 (-4) -7
-10 - 9 = -12 -7
-10 + (-9) = -12 + (-7)
-19 = -19
the mistake I made the first time I did it was in the part 3(-2 -2)
X does equal -2.
You just need to learn your integer rules.

ie. negative times negative = positive
and so on and so on.
2x-6-3x-15=3x-6-7 -x-21=3x-13 4x=-34 x=-8.5

This article contents is post by this website user, EduQnA.com doesn't promise its accuracy.

• Translating a function?
• How would you write the following text as an algebraic expression?
• Where can i get information on the novel entitled "the catcher in the rye"?
• Why is visiting the land of the midnight sun disastrous for Odysseus?
• What does it mean by "road-mapping a system of preference for importing Hawaiian goods by eliminating tarrifs"
• Fast Food Nation by Eric Schlosser...?
• How do you use the numbers 1,2,3,4 and total 26,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,and 50?
• Which of the folowing is false? Explain?